The Secretome of Hypoxia Conditioned hMSC Loaded in a Central Depot Induces Chemotaxis and Angiogenesis in a Biomimetic Mineralized Collagen Bone Replacement Material. Issue 2 (12th December 2019) - Quade, Mandy; Münch, Pina; Lode, Anja; Duin, Sarah; Vater, Corina; Gabrielyan, Anastasia; Rösen‐Wolff, Angela; Gelinsky, Michael
Abstract: The development of biomaterials with intrinsic potential to stimulate endogenous tissue regeneration at the site of injury is a main demand on future implants in regenerative medicine. For critical‐sized bone defects, an in situ tissue engineering concept is devised based on biomimetic mineralized collagen scaffolds. These scaffolds are functionalized with a central depot loaded with a signaling factor cocktail, obtained from secretome of hypoxia‐conditioned human mesenchymal stem cells (MSC). Therefore, hypoxia‐conditioned medium (HCM)‐production is standardized and adapted to achieve high signaling factor‐yields; a concentration protocol based on dialysis and freeze‐drying is established to enable the integration of sufficient and defined amounts into the depot. In humid milieu—as after implantation—signaling factors are released by forming a chemotactic gradient, inducing a directed migration of human bone marrow stroma cells (hBMSC) into the scaffold. Angiogenic potential, determined by coculturing human umbilical vein endothelial cells (HUVEC) with osteogenically induced hBMSC shows prevascular structures, which sprout throughout the interconnected pores in a HCM‐concentration‐dependent manner. Retarded release by alginate‐based (1 vol%) depots, significantly improves sprouting‐depth and morphology of tubular structures. With the intrinsic potential to supply attracted cells with oxygen and nutrients, this bioactive material system has great potential for clinical translation. Abstract : Biomimetic porous mineralized collagen scaffolds are functionalized with a central depot–loaded with the secretome of hypoxia‐conditioned mesenchymal stem cells (MSC). A sustained factor‐release and gradient formation induces directed MSC invasion and prevascular network formation towards the central depot in vitro. This concept is suggested to be a cell‐free and ready‐to‐use therapeutic solution for accelerated bone defect healing.